Extraction, Structural Characterization, and Immunomodulatory Activity of a High Molecular Weight Polysaccharide From Ganoderma lucidum - Liu, Guo; Zhang, Jun; Kan, Qixin; Song, Mingyue; Hou, Tao; An, Siyu; Lin, Hongyu; Chen, Hongzhang; Hu, Liuyun; Xiao, Jie; Chen, Yunjiao; Cao, Yong (Frontiers in Nutrition, 2022)
Ganoderma lucidum polysaccharides (GLP) exhibited excellent immunomodulatory activity. Unfortunately, its structure and immunomodulatory activity is still unclear. GLP was separated into two fractions (high Mw RGLP and low Mw EGLP) using 10 kDa cut-off ultrafiltration membrane. Although the RGLP content was low in GLP, the immunomodulatory activity in RGLP was significantly higher than that of EGLP. Moreover, RGLP was further separated via Sephacryl column to obtain RGLP-1 showed the best immunomodulatory activity in macrophage RAW264.7 model. Structural analysis revealed that RGLP-1 was 3978 kDa and mainly consisted of glucose. Periodate oxidation, Smith degradation and methylation results indicated that RGLP-1 is a β-pyran polysaccharide mainly with 13, 14, 16 and 13, 6 glycosyl bonds at a molar ratio of 40.08: 8.11: 5.62: 17.81. SEM, AFM and Congo red experiments revealed that RGLP-1 intertwined with each other to form circular aggregates and might possess a globular structure with triple-helix conformation in water. Overall, these results provide RGLP-1 as a potential functional food ingredient or pharmaceutical for immunomodulatory.